Mechanistic and therapeutic distinctions between cardiosphere-derived cell and mesenchymal stem cell extracellular vesicle non-coding RNA - Ann-Sophie Walravens (Nature Portfolio, 2021)
Abstract Cell therapy limits ischemic injury following myocardial infarction (MI) by preventing cell death, modulating the immune response, and promoting tissue regeneration. The therapeutic efficacy of cardiosphere-derived cells (CDCs) and mesenchymal stem cells (MSCs) is associated with extracellular vesicle (EV) release. Prior head-to-head comparisons have shown CDCs to be more effective than MSCs in MI models. Despite differences in cell origin, it is unclear why EVs from different adult stem cell populations elicit differences in therapeutic efficacy. Here, we compare EVs derived from multiple human MSC and CDC donors using diverse in vitro and in vivo assays. EV membrane protein and non-coding RNA composition are highly specific to the parent cell type; for example, miR-10b is enriched in MSC-EVs relative to CDC-EVs, while Y RNA fragments follow the opposite pattern. CDC-EVs enhance the Arg1/Nos2 ratio in macrophages in vitro and reduce MI size more than MSC-EVs and suppress inflammation during acute peritonitis in vivo. Thus, CDC-EVs are distinct from MSC-EVs, confer immunomodulation, and protect the host against ischemic myocardial injury and acute inflammation.